2018
DOI: 10.1002/jcp.27652
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: miR‐150 might inhibit cell proliferation and promote cell apoptosis by targeting LMO4 in Burkitt lymphoma

Abstract: This study aimed at investigating the effect of microRNA‐150 (miR‐150) on cell proliferation of Burkitt lymphoma and its molecular mechanism. Gene expression analysis was applied to identify target genes of miR‐150 in Burkitt lymphoma cell line ST486 based on the dataset from the Gene Expression Omnibus (GEO) datasets GSE86432. miRNA mimics, inhibitor and small interfering RNA (siRNA) were fluorescently labeled by Cy3, whereas plasmid vector was labeled by EGFP. Cells were viewed by fluorescence microscope and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Moreover, evidences have shown that VEGFA expression can be regulated by various microRNAs (miRNAs), including of miR-150, miR-22, miR-206 and miR-34a ( 33 36 ). Meanwhile, the levels of miR-150, miR-22, miR-206 and miR-34a have been found to be downregulated in human cancers ( 37 40 ). Thus, we investigated whether HHT combined with curcumin reduced VEGFA level in Raji cells by these miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, evidences have shown that VEGFA expression can be regulated by various microRNAs (miRNAs), including of miR-150, miR-22, miR-206 and miR-34a ( 33 36 ). Meanwhile, the levels of miR-150, miR-22, miR-206 and miR-34a have been found to be downregulated in human cancers ( 37 40 ). Thus, we investigated whether HHT combined with curcumin reduced VEGFA level in Raji cells by these miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…TP63 and LMO4 have been intensively studied as transcriptional targets in squamous cell carcinoma. They can regulate the expression of diverse tumor-related proteins and are involved in extracellular matrix and tumor microenvironment remodeling as well as in growth factor-mediated signal transduction [30,31,32]. Pathological specimens of HIV-related penile squamous cell carcinoma are very rare, so our sample size is relatively small, but the results obtained still have certain reference value.…”
Section: Discussionmentioning
confidence: 98%
“…TP63 and LMO4 have been intensively studied as transcriptional targets in squamous cell carcinoma. They can regulate the expression of diverse tumor-related proteins and are involved in extracellular matrix and tumor microenvironment remodeling as well as in growth factor-mediated signal transduction Zhang, 2019). Among the KEGG pathways, two terms linked to the regulation of cell proliferation and survival, including DNA replication and cell adhesion molecule metabolism, were identified.…”
Section: Discussionmentioning
confidence: 99%